IMPLEMENTATION OF RECIPROCAL TEACHING METHODS TO INCREASE SKILLS ANALYZING TEXT DRAMA AND STUDY LEARNING STUDENTS - Heryana, Rikki Faisa; Saktiyani, Aurelia; Mulhataeni, Desi (JLER (Journal of Language Education Research), 2018)
Students have difficulties in learning to analyze the drama text, from the initial observation done by the writer, the students consider the learning of analyzing the drama is easy learning, so the students tend to be lazy to learn and study it, the students feel that learning to analyze the drama text is easy to learn because the material has been studied when in junior high .Reciprocal Teaching method will be suitable for learning in analyzing drama text and increasing student independence. The method requires students to actively seek the material first to be delivered back to the students in front of the classThe research method used by the researcher is a qualitative method: Pre-Experimental design with One-Group Pretest-Postes Design research design. This method is done by taking preliminary data in the form of pre-test before the treatment, it is intended to measure the ability of students first to then be given treatment that is the application of learning by using methods Reciprocal Teaching, at the end of the treatment again given the final test or post-test, so the data comparison of students' ability before and after treatment.The result of the research is the average score of the students 'final test (post-test) which is higher than the pretest score of 7.31 and the average of the students' ability is 7.31% and there is significant difference between after and before the implementation of this method, that is t value (2,77)> t table (1,078) at 95% confidence level. This indicates that there is a positive result from the experiment of teaching and learning activity can work well, but the method has no correlation with the independence of learning, proved from the questionnaire of learning independence calculated using SPSS software there is a sig value. 0.157, which means the sig value. ie 0.157> 0.05.